Sustainable marketing activities, event image, perceived value and tourists' behavioral intentions in the sports tourism - Junfeng Wang; Vera Butkouskaya (Journal of Economics, Finance and Administrative Science, 2023)
Purpose - This study constructs the influence mechanism model of sustainable marketing activities (SMAs), event image, commemorative product perceived value and tourists' behavioral intentions (TBIs) in the sports tourism context of the Beijing Winter Olympic Games. Additionally, the article discusses the role of event image and product perceived value in enhancing the SMAs' effect on TBIs. Design/methodology/approach - The research analyzed 315 valid questionnaires from tourists in the Chinese market by structural equation modeling. Findings - The results indicate that SMAs positively impact sports tourism event image, tourists' perceived commemorative product value and TBIs. Meanwhile, event image and product perceived value mediate the SMAs and TBIs relationship. Research limitations/implications - Considering SMAs as essential for sustainable development, this paper contributes to the strategic management discipline. Additionally, the research expands the analysis of event image and product perceived value in the brand theory and customer behavior research. Practical implications - The article outlines the principal value of SMAs implementation in enhancing behavioral intentions. It also reveals that a favorable event image and good perceived value can enhance SMAs' effectiveness toward positively influencing TBIs, especially purchase intentions. It provides a new vision for nonprofit organizations to prioritize SMAs' implementation in marketing strategies. Originality/value - It is pioneering work with a complex research framework for SMAs implementation in the sports tourism context.
Keywords: M3; L83; Z30; 330; Sustainable marketing activities; Sports tourism; Event image; Perceived value; Behavioural intentions